The trade war between China and the United States and its consequences on Southeast Asian countries; a case study of Vietnam and Taiwan - Arsalan Ghorbani Sheikhneshin; Shirin Haddad Zand (رهیافتهای سیاسی و بین المللی)
The emergence of China's economic power, along with the decrease of America's share in global production and international trade, has led to a change in the geopolitical landscape of the world and in the economic balance in the international arena, which has finally brought the trade competition between China and America to its peak and it has emerged in the form of trade war. This matter caused Southeast Asian countries to become a field of economic conflict between China and America. The main question of this research is how the trade war between China and America has affected the economy of Southeast Asian countries?  In response to this hypothesis, it is investigated with an explanatory method that the trade war between China and America through trade tariffs and import restrictions leads to a change in imports-exports and trade deals with Southeast Asian countries, especially Vietnam and Taiwan. The purpose of this research is to explain China and America’s economic policy based on the strategy of neo-mercantilism in the form of the trade war and how this war has changed the economic balance in the whole world, especially in Southeast Asian countries.